ANALISIS STILISTIKA PADA NAMA DAN MAKNA: EMPAT KUMPULAN SAJAK KARYA AJIP ROSIDI DAN REKOMENDASINYA SEBAGAI MODUL AJAR PUISI DI SMA - Laudy, Fairuz Deliana; Nurhasanah, Een; Pratiwi, Wienike Dinar (Universitas Negeri Makassar, 2024)
This study aims to describe the form of language style in Nama dan Makna: Four Poetry Collections by Ajip Rosidi and its recommendation as a teaching module for poetry texts in high school. The method used in this research is descriptive method with qualitative data analysis. The stages of data analysis used in this study, researchers determine or examine the object of research that has been collected in the form of poetry texts, then analysed using stylistic analysis which focuses on finding and knowing the use of language styles used.The results of this study, in the poem Nama dan Makna: Four Collection of Poems by Ajip Rosidi, there are comparison language style, opposition language style, linking language style, and repetition language style. In the poem, the use of paralipsis language style is more dominant.